O corpo como laboratório de si: estudos fotográficos - Leticia Weiduschadt (2012)
This research is developed from the field of visual poetics related to the experience of my creation process. Crossed by theoretical and plastic questioning, it intends to open investigative possibilities for some relationships between the human body and photography. For this purpose, through the cartography of bodies, I analyze the changes in the notion of body ownership related to the absence of identity. Such notion promotes the research about the desire of deconstructing anatomic body parts. The deconstruction is consolidated in the fragmentation, in the metamorphosis, in the becoming animal; in conclusion, in the transgression of the canonical anthropomorphism. The experience of the view on the image and the theory of photography instrumentalize the study of the photographic gesture as a possibility of touching the materiality of the reproduction. In the wake of this touch notion, I investigate the skin as a body and photographic material wearing, as well as the limits of the encounter between image and support.